2020
DOI: 10.1371/journal.pone.0242354
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of commercial poultry farms in Mexico: Towards a better understanding of biosecurity practices and antibiotic usage patterns

Abstract: Mexico is one of the world’s major poultry producing countries. Two significant challenges currently facing the poultry industry are the responsible and judicious use of antimicrobials, and the potential occurrence of infectious disease outbreaks. For example, repeated outbreaks of highly pathogenic avian influenza virus subtype H7N3 have occurred in poultry since its first detection in Mexico in 2012. Both of these challenges can be addressed through good husbandry practices and the application of on-farm bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 65 publications
1
13
0
2
Order By: Relevance
“…In low and middle-income countries (LMICs), raising farmer awareness about the negative effects of untargeted AMU and promoting good farming practices, biosecurity, diagnostic services, and vaccination programs is essential [13]. Studies have shown that proper emphasis on hand hygiene at poultry farms and sensitization about biosecurity management can decrease AMU [43]. Initiatives to better inform farmers and veterinarians on appropriate AMU and farm biosecurity could help reduce AMU on farms [5].…”
Section: Farm Biosecurity (Or Management) Factors Affecting Antimicro...mentioning
confidence: 99%
“…In low and middle-income countries (LMICs), raising farmer awareness about the negative effects of untargeted AMU and promoting good farming practices, biosecurity, diagnostic services, and vaccination programs is essential [13]. Studies have shown that proper emphasis on hand hygiene at poultry farms and sensitization about biosecurity management can decrease AMU [43]. Initiatives to better inform farmers and veterinarians on appropriate AMU and farm biosecurity could help reduce AMU on farms [5].…”
Section: Farm Biosecurity (Or Management) Factors Affecting Antimicro...mentioning
confidence: 99%
“…The number of key variables is usually recommended to be 5 times less than the sample size (Alvarez et al, 2018). The other variables were removed because they were either compiled into a new one, correlated with other variables that were homogeneous in response, or not addressed by all respondents (Ornelas-Eusebio et al, 2020). The 3 groups were described from categories that were overexpressed (p-value less than 5%) in the group and they were transformed into a new variable called, ClusterTypo.…”
Section: Data Management and Analysismentioning
confidence: 99%
“…In the event of a negative outcome, different options can be applied, ranging from recommendations to penalties or even training of the farmer and personnel [ 13 ]. In previous publications, questionnaires or checklists proved to be useful tools for collecting data on biosecurity and assessing the compliance of poultry farms in the European Union (EU) [ 3 , 6 , 14 ] and in non-EU countries [ 11 , 12 , 15 , 16 ], highlighting potential deficiencies and opportunities for intervention.…”
Section: Introductionmentioning
confidence: 99%